2013
DOI: 10.1002/smj.2092
|View full text |Cite
|
Sign up to set email alerts
|

Are collective political actions and private political actions substitutes or complements? Empirical evidence from China's private sector

Abstract: This paper examines the circumstances under which collective and private corporate political actions are more likely to be substitutes or complements. Using data based on a series of nationwide surveys conducted on privately owned firms in China, I find that firms that are engaged in collective political actions are more likely to pursue private political actions. This positive relationship is stronger in less economically developed provinces and when there are greater opportunities for the state to redistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(174 citation statements)
references
References 85 publications
(164 reference statements)
2
161
0
8
Order By: Relevance
“…Marketization Index captures province-level market or institutional development across China using 5 factors: (1) government-market relations (intervention in markets), (2) share of non-stateowned enterprises, (3) level of development of product (and service) markets, (4) level of development of factor markets, and (5) level of development of market intermediaries and legal system. Several scholars have suggested that this index is a good proxy for government intervention (Cull and Xu 2005;Jia 2014;Tsai 2007), because it captures the role of the government in business from multiple perspectives. The higher the Marketization Index, the lower the government intervention within that region.…”
Section: Government Interventionmentioning
confidence: 99%
“…Marketization Index captures province-level market or institutional development across China using 5 factors: (1) government-market relations (intervention in markets), (2) share of non-stateowned enterprises, (3) level of development of product (and service) markets, (4) level of development of factor markets, and (5) level of development of market intermediaries and legal system. Several scholars have suggested that this index is a good proxy for government intervention (Cull and Xu 2005;Jia 2014;Tsai 2007), because it captures the role of the government in business from multiple perspectives. The higher the Marketization Index, the lower the government intervention within that region.…”
Section: Government Interventionmentioning
confidence: 99%
“…Firms' political activities constitute a dynamic capability that can create potential opportunities, reduce the threat of market entry, enhance firm legitimacy, and increase market share (Jia, 2013;Keim & Hillman, 2008;Li et al, 2013;Oliver & Holzinger, 2008;Sheng et al, 2011). They thus may contribute new insights into a firm's competitive advantage and innovation capabilities.…”
Section: Dual Capabilities and New Product Market Performance (Npmp)mentioning
confidence: 98%
“…However, these two forms might be unviable or even illegal in emerging economies such as China. Instead, firms in emerging economies may take such actions as building informal relationships with government officials (Peng & Luo, 2000) and participating in the parliament or other quasi-governmental organizations (Jia, 2014).…”
Section: Rgov As a Form Of Non-market Actionsmentioning
confidence: 99%